2017
DOI: 10.1128/msphere.00099-17
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Surveillance of Wastewater To Examine Seasonal Dynamics of Enterovirus Infections

Abstract: Enteroviruses are RNA viruses that are responsible for both mild gastroenteritis and mild respiratory illnesses as well as debilitating diseases such as meningitis and myocarditis. The disease burden of enteroviruses in the United States is difficult to assess because most infections are not recorded. Since infected individuals shed enterovirus in feces and urine, surveillance of municipal wastewater can reveal the diversity of enteroviruses circulating in human populations. Therefore, monthly municipal wastew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 53 publications
(33 reference statements)
6
61
1
Order By: Relevance
“…Nevertheless, EV-D68 was frequently detected in wastewater samples during reported outbreaks despite the fact that the virus is rarely found in stools from clinical cases (Barnadas et al 2017, Van Leer-Buter et al 2016). Although the presence of EV-D68 in sewage has been reported before (Benschop et al 2017, Brinkman et al 2017, Weil et al 2017), our finding was unexpected and suggests that EV-D68 might replicate in the gut more commonly than it is thought, perhaps during the initial stages of infection before respiratory symptoms develop and samples are collected for analysis. Although unlikely, the possibility that EV-D68 present in human respiratory fluids could reach the sewage system through washing, showering, etc.…”
Section: Resultssupporting
confidence: 46%
“…Nevertheless, EV-D68 was frequently detected in wastewater samples during reported outbreaks despite the fact that the virus is rarely found in stools from clinical cases (Barnadas et al 2017, Van Leer-Buter et al 2016). Although the presence of EV-D68 in sewage has been reported before (Benschop et al 2017, Brinkman et al 2017, Weil et al 2017), our finding was unexpected and suggests that EV-D68 might replicate in the gut more commonly than it is thought, perhaps during the initial stages of infection before respiratory symptoms develop and samples are collected for analysis. Although unlikely, the possibility that EV-D68 present in human respiratory fluids could reach the sewage system through washing, showering, etc.…”
Section: Resultssupporting
confidence: 46%
“…EV-D strains (all from serotype EV-D68) were only found in sewage samples from the United Kingdom. Studies using a variety of cell lines or direct molecular typing have shown the prevalence of EV-B strains in sewage in Europe and the United States (typically >75% of all EVs), with the occasional upsurge of EV-A and EV-D serotypes in recent years [ 15 , 21 ]. Interestingly, a recent study in Scotland identified a high quantity of EV-C strains in sewage samples (95 amplicons from 353 cloned EV sequences, 26.9%) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Next-generation sequencing (NGS) metagenomics and target-specific techniques have been described by us and others to detect EV strains in clinical and environmental samples [ 17–20 ]. However, the output from NGS analysis of uncultured EV strains present in sewage has been so far mostly restricted to information on the EV species or, in very few cases, the EV serotype composition [ 21 ], with insufficient nucleotide sequence information down to the genotype and strain level.…”
mentioning
confidence: 99%
“…While most infected people with non-polio enteroviruses have mild illness, these viruses can cause infections in infants and other immunocompromised individuals with serious complications [3]. Human enteroviruses are often detected in wastewater effluents [5][6][7]. Since 2003, these viruses have been listed on the United States Environmental Protection Agency (USEPA)'s Contaminant Candidate Water 2019, 11, 1131 2 of 8 List (CCL) as waterborne pathogens that could warrant inclusion in future regulations under the Safe Drinking Water Act [8].…”
Section: Introductionmentioning
confidence: 99%